Just beyond. Monstrosity - Stine, R. L. (KaBOOM!, 2021)
While her father and uncle renovate a 1950s Hollywood movie studio known for making horror flicks, siblings Ruthie and Ezra Dillon discover that the animatronic monsters featured in those old movies have come to life, and someone--with secrets to protect--is controlling them.